Energy Distribution of a Vehicle Shimmy System with the Delayed Tyre Model⁎. Issue 14 (2018) - Mi, Tian; Chen, Nan; Stepan, Gabor; Takacs, Denes
Abstract: A vehicle shimmy model using the Delayed Tyre Model to estimate the lateral tyre force is introduced. Stability charts are obtained for the linearized system. With reduced damping and stiffness parameters, a new vibration mode shows up at high speed range when the front wheels oscillate in opposite directions. Furthermore, the kinetic energy distributed on each generalized coordinate is calculated at the critical frequencies, and some suggestions are given on how to reduce shimmy in specific cases.